1987
DOI: 10.1242/jeb.132.1.223
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Agrin in Electric Organ Extracts and Localization of Agrin-Like Molecules in Muscle and Central Nervous System

Abstract: The portion of the muscle fibre's basal lamina that occupies the synaptic cleft at the neuromuscular junction contains molecules that cause the aggregation of acetylcholine receptors and acetylcholinesterase on regenerating muscle fibres. Agrin, which is extracted from basal lamina-containing fractions of the Torpedo electric organ and causes the formation of acetylcholine receptor and acetylcholinesterase aggregates on cultured myotubes, may be similar, if not identical, to the acetylcholine receptor- and ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The protein agrin, generated from motor neurons, was discovered in the extracellular matrix of the stone-ray electric ray's organ for generating electricity. 93 It plays a significant function in axon growth and projection and can be delivered to nerve terminals. Numerous early investigations have demonstrated that agrin was expressed in both SCs and neurons, indicating that agrin may be a promising target for peripheral neuroimaging.…”
Section: Axonal-related Tracers or Antibodiesmentioning
confidence: 99%
“…The protein agrin, generated from motor neurons, was discovered in the extracellular matrix of the stone-ray electric ray's organ for generating electricity. 93 It plays a significant function in axon growth and projection and can be delivered to nerve terminals. Numerous early investigations have demonstrated that agrin was expressed in both SCs and neurons, indicating that agrin may be a promising target for peripheral neuroimaging.…”
Section: Axonal-related Tracers or Antibodiesmentioning
confidence: 99%